The Rise of Arabic Literary Criticism in the Modern Era and Its Critics - M Rahim; Annisa Khairunnisa (Universitas Muhammadiyah Gorontalo, 2025)
Literary criticism in the Arab world experienced a very long journey in terms of the process of its emergence. The 5th and 6th centuries were the beginning of the golden age of Arabic literary criticism until the 12th century. In the 13th century to the 19th century during the Ottoman Turkish rule, Arabic literary criticism stagnated until the French seized power. During the French rule, Arabic literary criticism stretched until the collapse of France and the rise of Muhammad Ali as the ruler of Egypt which influenced the progress of modern Arabic literature. This study aims to examine the history of modern Arabic literary criticism, the factors of its rise, the trends of the era and the critics and their works and examples of criticism. This research uses library research with descriptive qualitative research. The technique used is content analysis. The results of this study, modern Arabic literary criticism in its history was influenced by Western literature, the French empire became a revival factor that influenced Arabic literary criticism from classical Arabic literary criticism to modern Arabic literary criticism through the introduction of French literature which was freer in style and language, trends in the modern era of classical literary criticism, westernists, assimilation of Arabic and Western, and fundamentalist Islamists, and critics with their works and examples of criticism.